PEDAGOGICAL SIGNIFICANCE OF TELEVISION SHOWS IN THE DEVELOPMENT OF SPEECH IN PRESCHOOL CHILDREN. (Universal International Scientific Journal, 2026)
In the context of rapid digitalization, television remains one of the most influentialsources of information and entertainment for preschool children. This study is devoted to examiningthe pedagogical significance of television programs in the development of speech among preschoolaged children. The main objective of the research is to analyze the impact of age-appropriate andeducational television content on children’s vocabulary development, pronunciation, coherent speech,and communicative competence. The research employed pedagogical observation, comparativeanalysis, and interviews with preschool teachers and parents. The findings show that educationaltelevision programs rich in meaningful content, clear pronunciation, and interactive elements have apositive influence on children’s speech development. Such programs support the acquisition of newvocabulary, contribute to correct pronunciation, and encourage children to express their thoughts morefreely and confidently. In addition, narrative-based programs with engaging characters expandchildren’s imagination and increase their communicative activity. At the same time, uncontrolledviewing and exposure to content that is not appropriate for children’s age may lead to a decrease inspeech activity and limit social interaction. Passive screen time without adult guidance reducesopportunities for active communication, which is especially important during the preschool period. Inconclusion, television programs can become an effective pedagogical tool in preschool education onlywhen they are carefully selected and used in moderation.
Keywords: preschool education; speech development; television programs